2013
DOI: 10.1017/jfm.2013.352
|View full text |Cite
|
Sign up to set email alerts
|

Riccati-less approach for optimal control and estimation: an application to two-dimensional boundary layers

Abstract: The control of Tollmien-Schlichting (TS) in a 2D boundary layer is analysed by using numerical simulation. Full-dimensional optimal controllers are used in combination with a set-up of spatially localised inputs (actuators and disturbance) and outputs (sensors). The Adjoint of the Direct-Adjoint (ADA) algorithm, recently proposed by Pralits & Luchini (2010), is used to efficiently compute the Linear Quadratic Regulator (LQR) controller; the method is iterative and allows to by-pass the solution of the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 42 publications
(63 reference statements)
2
41
0
Order By: Relevance
“…In fact when a full-order approach is adopted, no approximations are introduced on the open-loop linearised dynamics, thus avoiding the so-called spill-over effects due to the undesired excitation of those stable dynamics which have not been retained in the open-loop ROM and which can affect the control action. With the same purpose, a more general and computationally demanding full-dimensional approach to the LQG design has been recently investigated by Semeraro et al (2013) in the control of a two-dimensional boundary layer. In particular, the authors have shown that for such a highly convective system, when sensors are located downstream of the actuators, only a full-order compensator can always guarantees the stability of the closed-loop plant while varying the design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In fact when a full-order approach is adopted, no approximations are introduced on the open-loop linearised dynamics, thus avoiding the so-called spill-over effects due to the undesired excitation of those stable dynamics which have not been retained in the open-loop ROM and which can affect the control action. With the same purpose, a more general and computationally demanding full-dimensional approach to the LQG design has been recently investigated by Semeraro et al (2013) in the control of a two-dimensional boundary layer. In particular, the authors have shown that for such a highly convective system, when sensors are located downstream of the actuators, only a full-order compensator can always guarantees the stability of the closed-loop plant while varying the design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This is referred to in the literature as "reduce-then-design" process [44], and has seen several applications, both in numerical and experimental investigations [2,8,42,43]. An interesting reduced-order model for flow control is the Eigensystem realization algorithm (ERA), a technique proposed by Juang and Papa [24], that reproduces the input-output behaviour observed in a simulation or experiment without the need to solve adjoint equations.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Numerical modelling of fluid flows and mathematically rigorous theories for their control 4,5 have been usually first tested and verified in simplified conditions, at low or moderate Reynolds numbers. [6][7][8][9] Within this framework, the concept of structural sensitivity has gained interest with applications to a large variety of globally unstable flows. [10][11][12][13][14][15] Indeed this linearised approach allows one to predict, beforehand, the effective positioning of a flow disturbance, i.e., a passive device, able to shift the vortex-shedding frequency or even to completely suppress the global instability of the flow.…”
Section: Introductionmentioning
confidence: 99%